Potential of cypermethrin or diazinon and their combined action with piperonyl butoxide (PBO) against Periplaneta americana L (University Journal of Zoology, Rajshahi University, 2009)
No Abstract Key words: Periplaneta americana, diazinon, cypermethrin, LD50, synergist doi:10.3329/ujzru.v27i0.1966 Univ. j. zool. Rajshahi Univ. Vol. 27, 2008 pp. 101-102